At-Ta’abbud and at-Ta’aqqul in Islamic Law and Their Relevance to the Implementation of Law Number 33 of 2014 Concerning Guarantee of Halal Products - Arifin, Zarul; Hasan, Maisyarah Rahmi (ADDIN, 2023)
This writing discusses ta’abbudi and ta’aqquli in Islamic jurisprudence, aiming to provide comprehensive insight into both of these terms. Positioning oneself as a mukallaf (a responsible and accountable individual), on one hand, acknowledges that acts of worship (ta’abbudi) must be fully accepted, whether or not one comprehends their meanings, as they are divine commands. Similarly, on the other hand, a mukallaf is granted the authority and capability to employ reason in dealings with worldly matters (mu’amalah), enabling the development of laws in accordance with the changing times. In the context of Law Number 33 of 2014 on Halal Product Assurance, at-Ta’abbud and at-Ta’aqqul hold significant relevance. Article 10, paragraphs (1) and (2), regulate the requirements for halal products, encompassing raw materials, production processes, storage, as well as processing, handling, and packaging procedures. This indicates that at-Ta’abbud plays a crucial role in ensuring compliance with halal product requirements. Furthermore, Article 10, paragraph (3), emphasizes that halal products must be verified by accredited halal certification bodies. This underscores the importance of at-Ta’aqqul in analyzing and verifying the halal status of products.